Exploring the Influence of Good Governance, Church Management and Structure on the Development and Growth of the Church - (:unkn) unknown (My University, 2021)
In every sphere of life, supervision is an avenue to build on ones' aptitude and knowledge to grasp the future. The sustenance of the future is proportional to the effective Management of resources and personality. The Church’s growth has been stagnant in recent times. One would question from a business-perspective how the Church has been managed over the years. Does Management concern the Church? Management, as a business function provides leadership support to organizations' resources to realize strategic goals and objectives. Although churches are not precisely business organizations tied with specific management practice as requirements including other complex legal requirements such as filing returns and payment of taxes, they engage in activities that require adequate planning and execution if they are to be successful and impact to the Church's growth and development. Hence, there is a need for an effective governance system for churches that will ensure efficient and effective utilization of resources and management practices in the growth and development of Churches. This paper, therefore, aimed at presenting an analysis of good Governance, effective managerial strategies and church structure for church growth and development. The study employed the use of content analysis of literature as the main components in the study in the areas of effective managerial practices, corporate Governance and organizational Structure and its impact on Church growth and development. The study systematically answered various questions under the study, which eventually contributes towards the establishment of good Governance, effective management and Church Structure on the growth and development of Churches. The study, therefore, unearthed the relationship between good Governance, church management and Structure on the growth and development of churches. It further made a recommendation for leaders of churches on the elements of good Governance, Management an
Keywords: African Research